Country-level differences in the electrified kilometers of plug-in hybrid electric vehicles across Europe - Mandev, Ahmet; Sprei, Frances (Environmental research, infrastructure and sustainability : ERIS, 2024)
Plug-in hybrid electric vehicles (PHEVs) have been the subject of many debates regarding their role in the electrification of the transport sector for the duality that they can be subsidized due to electric driving, but they can also be driven on fossil fuels. Previous studies focused on the charging and driving behavior of PHEVs to assess their share of electrified kilometers (vehicle kilometers travelled (VKT) with the internal combustion engine off—thus relying only on the electric engine—among all VKT), and to determine their environmental benefits. However, there is limited understanding of how the same vehicle is used in different countries and what that means in terms of the share of electrified kilometers. In this study, we analyze a very large real-world sample (over 32 000 vehicles) of an identical PHEV model to understand how PHEV driving differs in the share of electrified kilometers among 10 European countries and what country-level factors are behind these differences. We find that there is a North–South divide in the share of electrified kilometers within Europe, with a significant decrease southward. Furthermore, at the country-level, a higher share of company cars can be associated with higher shares of electrification contrary to expectations in the literature, highlighting the importance of increased opportunities and incentives for workplace charging and less subsidies for conventional fuel use. We also find that higher electricity prices are associated with lower shares of electrified kilometers at the country-level. Furthermore, PHEVs in our dataset, in all countries have consistently 20% to 40% lower shares of electrified kilometers compared to type-approval values in Europe.